New benzotriazole derivatives as multifunctional ligands - Thomas, Christophe M.; Therrien, Bruno; Neels, Antonia; Stoeckli-Evans, Helen; Süss-Fink, Georg (My University, 2002)
New multifunctional ligands based on the benzotriazole unit were synthesized by condensation of hydroxymethylbenzotriazole with carboxylic acid derivs. of pyridine, PPh3, ferrocene and thiophene. The coordination properties of these ligands towards Co, Rh and Ir were studied. [on SciFinder(R)]
Keywords: benzotriazole deriv multifunctional ligand prepn transition metal complex; crystal structure benzotriazole deriv multifunctional ligand transition metal complex